Fecal occult blood test: Is it still worth it for colorectal cancer screening? - (:unkn) unknown (My University, 2023)
Introduction: One of the most critical factors determining survival in cases of colorectal cancer is diagnosis and treatment at an early stage. Diagnosis at an early stage is possible with screening programs carried out within preventive health services. Aim: In this study, we aimed to compare the results of patients who underwent colonoscopy because of a positive fecal occult blood test (FOBT) with those over 50 years of age who underwent colonoscopy due to other complaints and to reveal whether an FOBT test is still essential for screening programs. Methods: This study included patients who underwent colonoscopy between January 2016 and December 2021. The patients were analyzed in two groups, according to the reasons for colonoscopy: Group I (FOBT-positive) and Group II (other reasons). Results: A total of 3393 patients were included in the study. They were divided into two groups for evaluation: those who underwent colonoscopy after a positive FOBT (Group I) and patients over 50 years of age who underwent colonoscopy for other reasons (Group II). When the colonoscopy findings were compared between the groups, inflammatory bowel disease (p = 0.03) was more prevalent in Group I, while normal colonoscopy (p = 0.03) was found to be more common in Group II. Polyps, malignancy, diverticulosis, and perianal diseases appeared to be statistically similar between the groups. Conclusion: FOBT can still be used in colorectal screening because it is inexpensive and widely available, is more acceptable to patients due to its non-invasiveness, and can be applied outside of clinical settings.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery; colonoscopy; colorectal cancer; fecal occult blood test; screening